Analysis of Islamic Financial Literacy of MSMEs in Yogyakarta - ismail, syadan hussein; setiartiti, lilies (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to evaluate the specific attributes of MSMEs in Yogyakarta and analyze the factors influencing their level of Islamic financial literacy. The study also examines how these enterprises perceive and apply these factors to support their business development. Data were collected through surveys and in-depth observations to address the issues faced and explain the observed phenomena. The findings reveal that the majority of MSMEs do not utilize financial statements or accounting information for decision-making related to their business development, considering such information unnecessary. This research offers critical insights for policymakers, highlighting potential strategies to enhance financial literacy among MSMEs. Improved financial literacy is crucial for MSMEs to navigate financial challenges, access diverse funding sources, and make informed financial decisions. By understanding and implementing financial management practices, MSMEs can better position themselves for sustainable growth and development. The study underscores the importance of targeted educational programs and policy interventions to bridge the financial literacy gap, thus empowering MSMEs to contribute more effectively to the economy. Overall, the results suggest that increasing the financial literacy of MSMEs is a vital step towards fostering a more inclusive and robust economic environment in Yogyakarta.